Developing an Optimization Model to Manage Unpaved Roads - Promothes Saha; Khaled Ksaibati (Journal of Advanced Transportation)
While approximately two-thirds of the total centerline miles are unpaved in the state of Wyoming, there is no optimization program for managing these roads. Unlike paved roads, unpaved roads deteriorate from excellent to failed conditions in sometimes less than a year. This deterioration rate necessitates developing a novel methodology for managing them efficiently. When funding is limited, it is important to identify the best mix of road preservation projects that provides the most benefits to society in terms of overall life cycle cost of the road network. This research intends to develop a management system using optimization techniques for managing unpaved roads within limited budget. The common factors that play the most important role for identifying projects are road condition parameters, unpaved road deterioration model, treatment types, cost-factors associated with selecting treatment types, traffic counts, budget, and treatment cost. Road condition parameters include cross section, roadside drainage, rutting, potholes, loose aggregate, dust, corrugation, and ride quality. This methodology will facilitate a statewide implementation of unpaved road management system for counties in Wyoming. The methodology can be easily adopted by other states interested in the management of gravel roads.